2013
DOI: 10.15332/us.v12i2.1214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia De Caries De La Infancia Temprana Y Factores De Riesgo Asociados en Niños De 1 a 5 Años en La Ciudad De Santiago De Cali

Abstract: RESUMENObjetivo: determinar la prevalencia de Caries de la Infancia Temprana (CIT) en niños de 1 a 5 años de la ciudad de Cali y describir los factores de riesgo asociados. Materiales y métodos: se realizó un estudio descriptivo transversal, de prevalencia con todas las instituciones educativas inscritas en la Secretaría de Educación. La muestra la constituyeron 929 menores a quienes se les indagó mediante un cuestionario dirigido a sus padres, acerca de los factores de riesgo asociados con caries dental. Se r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…During the comparison of the results, it was found that the largest number of infants affected by early caries was of males, being 53.92%, compared to the girls, 46.08%, although there was no relationship between gender and prevalence of dental caries. Similar results were found in previous studies [19,33,34].…”
Section: Discussionsupporting
confidence: 93%
“…During the comparison of the results, it was found that the largest number of infants affected by early caries was of males, being 53.92%, compared to the girls, 46.08%, although there was no relationship between gender and prevalence of dental caries. Similar results were found in previous studies [19,33,34].…”
Section: Discussionsupporting
confidence: 93%